Analisis Penyebab Rendahnya Penggunaan Dompet Elektronik (E-Wallet) Berdasarkan Kelompok Umur Di Indonesia - Khaira, Mulil; Dirgahayu, R Teduh; Hidayat, Taufiq (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The number of internet users in Indonesia are high, but there is a gap in the number of users e-wallet based on age groups in Indonesia. For example, the low use of e-wallets among the 18-24 year age group and among the 40-year-old age group. Even though e-wallets offer many benefits for their users. Therefore, this study aims to determine the factors causing the low use of e-wallets among the 18-24 year age group and those over 40 years of age. This study uses UTAUT2 as the basic framework and the Security variable as an additional variable. Data collection was carried out online using google form to 117 respondents. The software for data analysis is SmartPLS. The results in the 18-24 year age group are Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value and Habit affect Behavioral Intention positively and Facilitating Conditions, Behavioral Intention affect Use Behavior positively. Whereas in the age group over 40 years, Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Security affect Behavioral Intention positively and Facilitating Conditions, Habit, Behavioral Intention affect Use Behavior positively.